Pemenuhan Hak Ganti Rugi Jemaah Umrah sebagai Konsumen dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen (Studi Kasus PT Khazanah Tamma Internasional) - Frengky Mahulette; Muhammad Hazmi Adzhani; Yuyut Prayuti (AHKAM, 2026)
The organization of Umrah pilgrimage travel constitutes a religious service that establishes a legal relationship between Umrah pilgrimage travel organizers (PPIUs) and pilgrims as consumers. However, cases of failure to depart, departure delays, and embezzlement of funds continue to cause material and immaterial losses to pilgrims and demonstrate that consumer rights have not been fully fulfilled. This study aimed to analyze the responsibility of business actors in fulfilling Umrah pilgrims’ right to compensation under Law Number 8 of 1999 concerning Consumer Protection through a case study of PT Khazanah Tamma Internasional. This study employed a normative legal method using statutory, conceptual, and case study approaches. Research materials were collected through a literature review of legislation, scientific journals, and news reports related to the PT Khazanah Tamma Internasional case and were then analyzed normatively. The findings showed that PT Khazanah Tamma Internasional, as a business actor, was legally responsible for providing compensation, damages, and/or replacement to pilgrims for losses arising from the failure to provide the services as agreed. This responsibility was based on Article 19 of Law Number 8 of 1999 concerning Consumer Protection. However, fulfilling the right to compensation faced obstacles in the form of the company’s limited assets, lengthy legal proceedings, and weak oversight of PPIUs. This study concludes that the regulation of business actors’ responsibility has provided a legal basis for protecting pilgrims, but the effectiveness of its implementation still needs to be strengthened. These findings imply the need to enhance government oversight and develop more effective legal protection mechanisms to ensure the fulfillment of pilgrims’ rights as consumers of religious services.